OPTIMIZATION OF LOGISTICS PROCESSES IN INTEGRATED AGRICULTURAL PRODUCTION ENTERPRISES - RYZHOVA, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to analyze ways to increase the efficiency of logistics process management, taking into account the trends in the development of the economic system at the global level, as well as the specifics of the functioning of integrated agricultural production enterprises. The research is based on the hypothesis that the concept of logistics supply chain management is most promising in outlining directions for optimizing logistics processes in the context of a change in business philosophy (circular economy concepts gaining relevance), as well as the development of mechanisms of competitive interaction, which translates the system into the paradigm of the inverted pyramid of management with an emphasis on the transformation of the understanding of the role of sales activity - the departure from its identification as an operational function, the transition to the inclusion of sales activity as strategic tools for achieving the general goals of organizations connected by the chain of creation of added value. The conceptual differences between "logistics" and "supply chain management" are revealed. The peculiarities of the functioning of integrated agrarian enterprises were studied, among which a characteristic feature was highlighted, which is the concentration of a significant part of the movement of the material flow within the internal borders. A conclusion was made about the actualization of the issue of combining internal logistics with managing relations with external partners for the mentioned business entities to achieve a synergistic effect and increase the overall efficiency of implementing business processes. The impact of modern challenges on the internal logistics of integrated agricultural production enterprises was analyzed, and the definition of vectors of its transformation was considered, considering circular and bioeconomy paradigms. The critical elements of the sales policy development strategy are presented, including the creation of a centralized data management system, digitalization of the performance of individual logistics functions, and adaptation to the specifics of agricultural production.
Keywords: agricultural production; integrated enterprises; logistics; logistics activity; management of logistics supply chains; sales activity